2015
DOI: 10.1038/emm.2015.68
|View full text |Cite
|
Sign up to set email alerts
|

Serum exosomal microRNAs as novel biomarkers for hepatocellular carcinoma

Abstract: Recent studies have shown that circulating microRNAs are a potential biomarker in various types of malignancies. The aim of this study was to investigate the feasibility of using serum exosomal microRNAs as novel serological biomarkers for hepatocellular carcinoma (HCC) in patients with chronic hepatitis B (CHB). We measured the serum exosomal microRNAs and serum circulating microRNAs in patients with CHB (n=20), liver cirrhosis (LC) (n=20) and HCC (n=20). Serum exosomal microRNA was extracted from 500 μl of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
249
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(264 citation statements)
references
References 48 publications
5
249
0
3
Order By: Relevance
“…It was reported that miR-21 and miR-1246 were enriched in human breast cancer [66]. Sohn W's studies revealed that the levels of circulating exosomal miR-181, miR-221, and miR-224 were significant higher in HCC patients than in chronic hepatitis B patients; however, there were little differences in the level of circulating miRNAs between these two groups [67]. The level of circulating exosomal miR-10b and miR-30c was significantly elevated in 29 PDAC patients relative to chronic pancreatitis patients; however, the level of CA 19-9 was normal or slightly increased in 8 cases [68].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that miR-21 and miR-1246 were enriched in human breast cancer [66]. Sohn W's studies revealed that the levels of circulating exosomal miR-181, miR-221, and miR-224 were significant higher in HCC patients than in chronic hepatitis B patients; however, there were little differences in the level of circulating miRNAs between these two groups [67]. The level of circulating exosomal miR-10b and miR-30c was significantly elevated in 29 PDAC patients relative to chronic pancreatitis patients; however, the level of CA 19-9 was normal or slightly increased in 8 cases [68].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that miR-224 may be a prospective biomarker for the diagnosis of HCC [41-43]. Okajima et al [44] performed a systematic review of microRNAs in plasma and identified miR-224 as a sensitive biomarker for detecting and monitoring HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The level and type of miRNA in the exosomes found in the serum of HCC patients differ significantly the miRNA in the serum exosomes of normal healthy individuals (67)(68)(69)(70). For instance, HCC patients with larger tumors and those with recurrent HCC after liver transplantation had lower levels of miR-718 in serumderived exosomes.…”
Section: Exosomes As Biological Markersmentioning
confidence: 93%